2018
DOI: 10.1159/000482008
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Human Papillomavirus Infection for Spontaneous Abortion, Spontaneous Preterm Birth, and Pregnancy Rate of Assisted Reproductive Technologies: A Systematic Review and Meta-Analysis

Abstract: Aims: To estimate the impact of human papillomavirus (HPV) infection on spontaneous abortion, spontaneous preterm birth (sPTB), pregnancy rate of females undergoing assisted reproductive technologies (ART), and spontaneous abortion of ART pregnancy. Methods: PubMed, Medline, Embase, and the Cochrane Library were searched until December 16, 2016. The OR or relative risk (RR) with its corresponding 95% CI were selected as effect size. Subgroup analysis of HPV genotype infection (high-risk HPV [HR-HPV] or indiscr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 36 publications
5
33
0
Order By: Relevance
“…It was found that HR-HPV infection was a risk for sPTB. Moreover, HPV infection was found to be independent of the clinical pregnancy rate and spontaneous abortion [ 52 ], results similar to those of Siristatidis and colleagues. These two meta-analyses revealed that there is no evidence to blame HPV for ART outcome, apart from the preterm delivery.…”
Section: Hpv and Assisted Reproductive Technology (Art)supporting
confidence: 72%
See 1 more Smart Citation
“…It was found that HR-HPV infection was a risk for sPTB. Moreover, HPV infection was found to be independent of the clinical pregnancy rate and spontaneous abortion [ 52 ], results similar to those of Siristatidis and colleagues. These two meta-analyses revealed that there is no evidence to blame HPV for ART outcome, apart from the preterm delivery.…”
Section: Hpv and Assisted Reproductive Technology (Art)supporting
confidence: 72%
“…Further to the above founding, it was also reported that when HPV infection is present in the male partner, it appears that there is a negative effect on live birth/ongoing pregnancy rate and an increase in the miscarriage rate [ 51 ]. Lastly, following the previous novel meta-analysis, Xiong and colleagues [ 52 ], performed another meta-analysis relating the HPV risk with spontaneous abortion and spontaneous preterm birth (sPTB). It was found that HR-HPV infection was a risk for sPTB.…”
Section: Hpv and Assisted Reproductive Technology (Art)mentioning
confidence: 99%
“…Although previous meta-analyses have established an association between HPV infection and both male infertility (Lyu et al, 2017) and the outcomes of natural or IVF/ICSI pregnancies (Siristatidis et al, 2018;Xiong et al, 2018), little is known regarding its role in female infertility. This is thought to be the first meta-analysis of studies comparing the prevalence of HPV infection in the infertile and general female population.…”
Section: Discussionmentioning
confidence: 99%
“…Two meta-analyses have also demonstrated an association between HPV infection and IVF/intracytoplasmic sperm injection (ICSI) outcome. Xiong et al (2018) found that infection with the indiscriminate HPV genotype increased the risk of spontaneous abortion, and HR-HPV infection was a risk factor for spontaneous preterm birth. However, there is not enough evidence to indicate an association between HPV infections and the pregnancy or spontaneous abortion rates of ART (Siristatidis et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Although a significant number of viral taxa have been detected in amniotic fluid, only a few such as herpes simplex virus, adenovirus, enterovirus and cytomegalovirus have been linked to PTB (59). Viral infections of the lower reproductive tract can also predispose to PTB, with several studies implicating cervical human papillomavirus (HPV) (60,61) and herpes simplex virus (HSV) (62,63) in the aetiology of PTB.…”
Section: Discussionmentioning
confidence: 99%